Global Proteomic Analysis Reveals Widespread Lysine Succinylation in Rice Seedlings - Zhang, Kai (Int J Mol Sci, 2019)
Lysine succinylation (Ksu) is a dynamic and reversible post-translational modification that plays an important role in many biological processes. Although recent research has analyzed Ksu plant proteomes, little is known about the scope and cellular distribution of Ksu in rice seedlings. Here, we report high-quality proteome-scale Ksu data for rice seedlings. A total of 710 Ksu sites in 346 proteins with diverse biological functions and subcellular localizations were identified in rice samples. About 54% of the sites were predicted to be localized in the chloroplast. Six putative succinylation motifs were detected. Comparative analysis with succinylation data revealed that arginine (R), located downstream of Ksu sites, is the most conserved amino acid surrounding the succinylated lysine. KEGG pathway category enrichment analysis indicated that carbon metabolism, tricarboxylic acid cycle (TCA) cycle, oxidative phosphorylation, photosynthesis, and glyoxylate and dicarboxylate metabolism pathways were significantly enriched. Additionally, we compared published Ksu data from rice embryos with our data from rice seedlings and found conserved Ksu sites between the two rice tissues. Our in-depth survey of Ksu in rice seedlings provides the foundation for further understanding the biological function of lysine-succinylated proteins in rice growth and development.